2008
DOI: 10.1016/j.yhbeh.2007.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Rapid effects of estradiol on male aggression depend on photoperiod in reproductively non-responsive mice

Abstract: In three genuses and four species of rodents, housing in winter-like short days (8L:16D) increases male aggressive behavior. In all of these species, males undergo short-day induced regression of the reproductive system. Some studies, however, suggest that the effect of photoperiod on aggression may be independent of reproductive responses. We examined the effects of photoperiod on aggressive behavior in California mice (Peromyscus californicus), which do not display reproductive responsiveness to short days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 55 publications
11
107
0
1
Order By: Relevance
“…S8). Our findings are consistent with our learning effects, and with other data demonstrating estrogens begin to affect sexual behavior and aggression ∼15 min after administration (26,27).…”
Section: Discussionsupporting
confidence: 93%
“…S8). Our findings are consistent with our learning effects, and with other data demonstrating estrogens begin to affect sexual behavior and aggression ∼15 min after administration (26,27).…”
Section: Discussionsupporting
confidence: 93%
“…in long (16 h light:8 h dark) and winter-like short days (8 h light:16 h dark). Estradiol injection into male P. polionotus experiencing short days increases aggressive behavior within 15 min [37] , but there is no signifi cant effect on behavior during long days. These results suggest that estradiol increases aggression during short days in mice by activation of a non-genomic mechanism, as it is generally thought that 15 min is insufficient for gene expression changes mediated by estrogen receptors [38] .…”
Section: Discussionmentioning
confidence: 93%
“…There is evidence that estradiol induces anxiolytic behavior [16,36] . The non-genomic effects of estradiol have been studied by Trainor et al [37] . Estradiol has rapid effects on the behavior of male deer mice (Peromyscus sp.)…”
Section: Discussionmentioning
confidence: 99%
“…Female-female aggression in Syrian (Fleming et al 1988) and Siberian (Scotti et al 2007) hamsters is also increased under short days. In hamsters and Peromyscus, studies using c-fos as an indirect marker of neuronal activity found no differences in c-fos expression in several brain regions between long day and short day aggression tested males (Kramer et al 2008;Trainor et al 2008), even though short day males were more aggressive. We recently used measurements of phosphorylated extracellular signalregulated kinase (pERK, also known as mitogen activated protein kinase or pMAPK) as an alternative marker of brain activity (Trainor et al 2010).…”
Section: Introductionmentioning
confidence: 91%